Effects of Nb–Ti double microalloying on the grain structure and precipitates of hot compressed FeCrAl alloys - Xing Fan; Fei Wang; Hongming Wang; Bowen Zhao; Runze Li; Jun Zhou (Journal of Materials Research and Technology)
Grain coarsening significantly weakens the strength and toughness of FeCrAl alloys at high temperatures. This study focused on the grain refinement behaviour of a Nb–Ti double-microalloyed FeCrAl alloy (Fe–18Cr–6Al‒0.2Ti‒0.2Nb) after hot compression, and the further development of recrystallization grain size during heat treatment was also explored at temperatures of 1100 °C and 1250 °C for 1 and 6 h. Strain-induced Nb-rich and Ti-rich precipitates located at grain boundaries and/or subgrain boundaries influenced dynamic recrystallization during hot compression regardless of parameters such as the strain rate and initial grain size. Additionally, incomplete recrystallization was observed at 1100 °C, with a limited increase in the grain size and a decrease in the size and volume fraction of the Nb-rich and Ti-rich precipitates. Increasing the heating temperature accelerated discontinuous recrystallization, leading to a decrease in the internal dislocation density and hardness. This indicates that the addition of Nb and Ti significantly refined the recrystallized grain size while limiting their growth at high temperatures, which improved the mechanical properties of the Nb–Ti–FeCrAl alloy in high-temperature applications.